O-B05 Does rapid or gradual weight loss following bariatric surgery affect lean body mass depreciation?. (16th December 2021) - Sivakumar, Jonathan; Chen, Qianyu; Read, Matthew; Sutherland, Tom; Ward, Salena; Chong, Lynn; Hii, Michael
Abstract: Background: Controversy exists regarding the influence of the rate of weight loss on long-term body composition. The objective of this study was to compare body composition changes in patients with successful and unsuccessful weight loss 12 months after bariatric surgery. Methods: A prospective analysis was completed on patients undergoing bariatric surgery at St Vincent's Hospital Melbourne between 2017 and 2021. Body composition was measured with dual-energy X-ray absorptiometry immediately before surgery, and at 12 months post-operatively. Fat mass (FM), lean body mass (LBM) and skeletal muscle index (SMI) trajectories were analysed between patients, with either successful weight loss (SWL) or unsuccessful weight loss (USWL) stratified based on an excess weight loss (EWL) threshold of ≥ 50%. Results: Thirty-seven patients were included in this series (SWL n = 25, USWL n = 12). Compared to those with USWL, SWL demonstrated a greater mean loss in BMI (12.3 vs 7.3 kg/m 2 ; p < 0.001) and weight (34.4 vs 20.3 kg; p < 0.001). SWL demonstrated a significantly greater reduction in tissue fat% than USWL, with patients losing 7.3% more tissue fat on average. SWL was associated with an improved mean SMI% when compared with USWL (5.5 vs. 2.42%; p < 0.0009). However, the difference in FM:LBM loss ratio between the two groups did not demonstrate statistical significance (7.07 vs 4.62, p = 0.2519). Conclusions: This data suggests that SWL is associated with a more optimal body composition outcome than USWL, which is at least partly due to a relative skeletal muscle-sparing effect in this group. Further research is warranted in understanding the implications of these changes on resting energy expenditure and the risk of weight regain.